MODAL SOSIAL DALAM RELASI KERJA TUPPERWARE PT. RIAU CAHAYA UTAMI DI KOTA PEKANBARU - Friday Meliani Banjar Nahor; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Pekanbaru on PT. Riau Cahaya Utami tupperware member. The purpose of this research is to know the forms of social capital in tupperware marketing network by PT. Riau Cahaya Utami member in Pekanbaru City. The focus of this research is the characteristic of tupperware marketing network by PT. Riau Cahaya Utami member in Pekanbaru City. This research was conducted on five members of tupperware determined using purposive sampling technique. Research instances use observation, in-depth interviews and documentation. This research uses qualitative analysis technique. Research conducted found that there are some characteristics of tupperware marketing network, namely: Source of capital, for business capital research subjects average using their own money. Selling price, for the selling price there are some research subjects who sell based on the price of the company and there are set their own prices. and Sales systems, research subjects conduct sales systems by promoting in social media, credit systems and catalogs. The study also found there are some social capital contained in tupperware marketing, namely: social networking, trust, reciprocity, and proactive actions. Keywords: Social Capital, Social Networking, Tupperware Pekanbaru